47. Wiki Products: A comparison - Challborn, Carl; Reimann, Teresa (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Report #27 in this series discussed the 'wiki' method of online information-sharing, and its educational uses. A wiki is browser-based collaborative writing environment, in which a community may amass and exchange information on a particular topic, and to which anyone may contribute without having Web programming skills. In the current study, seven wikis are reviewed: EditMe, MediaWiki, seedwiki, Socialtext, Swiki.net, and WikkiTikkiTavi/ InterWiki. The educational potential of each is discussed.